An Approach to Good Governance Management for Private Charity Schools of Buddhist Temple in Central Region - จิตต์ประยูร ปรรญฐ์จพลธ์ (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
The purposes of this research were to study the circumstance and implementation of educational administration on an approach to good governance management for private charity schools of Buddhist temple in central region. The research methodology were consist of two procedures 1) to study the circumstance of educational administration on an approach to good governance management for private charity schools of Buddhist temple in central region. This research was studied by the all participants comprised 344 persons. The research instruments were questionnaire with five-level scale and the reliability is 0.93. Frequency distribution, percentages, mean, and standard deviations were used in the data analysis and research statistics. 2) to find the way by organizing group discussion sessions and using content analysis. Criteria for selection experts are six school administrators under the Central School of Buddhism, one teacher that has skill in school administration, seven school administrators that graduate in master degree, and one academician from the Office of the Private Education Commission (PSO), Ministry of Education. Total of the experts are 16 people. The research findings were: 1) the circumstance on an approach to good governance management for private charity schools of Buddhist temple in central region. Overall, it was at the highest level. The highest level of governance management which was the value, responsibilities, transparency, participation and moral. On the other side, the aspect that is governed by the least good governance is the rule of law. 2) an approach to good governance management for private charity schools of Buddhist temple in central region and the procedure of the educational administration was issuing regulations by attended the rights and responsibilities and updating rules or regulations to serve current situations which may change. Also, encouraging the management to adhere to the moral principles of the administration with honesty, adherence to the accuracy, transparency, reliability. It can be monitored and monitored internally and externally to meet the quality assurance requirements of the educational institution. As an opportunity for all parties can be participated. And promote mutual consciousness in the use of resources, the philosophy of sufficiency economy is worth. The budget plan for the allocation of educational resources for the administration to maximize the benefits.